(3JaSjQ dZI CjgG GdhdO ddZRGdjs - (3eLghds
(3ChdgG (B:s
(3gPG GdZI CjgG GdhdO GdMeO ddg eSJajOG ObGFb NWQ HGd UQa QjYGf Cj GSJeQGQ CSfafG GdJeGS Sdhc GMHGs
(3BNQgG (B:s
(3GHQGO CTQGQ GYJb QbGHs
(3Hjf GdSWhQ JQLeI HGddZI GdaGQSjI, hgh HGddZI GdYQHjI hGdaGQSjI hgPG GdeNWhW JQLeI dHYV eaQOGJ cJGH (B((3CjgG GdhdO(B) (3dMLI GdESdGe CHj MGeO GdZRGdj Edi GddZI GdJQcjIs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
Keywords: (3GddZIs